2020
DOI: 10.1002/acm2.13011
|View full text |Cite
|
Sign up to set email alerts
|

A novel and effective method for validation and measurement of output factors for Leksell Gamma Knife® Icon™ using TRS 483 protocol

Abstract: The objective of this work was to identify the exact location of the effective point of measurement (EPM) of four different active detectors to compare the relative collimator output factors (ROF) of Leksell Gamma Knife (LGK) according to IAEA TRS‐483 recommendations. ROF was measured at the center of the spherical LGK‐Solid Water (LGK‐SW) Phantom for three (4‐, 8‐, and 16‐mm in diameter) collimators using four (PTW‐TN60008, PTW‐TN60016, PTW‐TN60017, and PTW‐60019 diode/diamond) detectors. Since diode detector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The OF 4 value obtained using EBT films agreed with the LGP value (Figure 8). Cyriac et al measured OF 4 using T60019 and the TRS-483 OCFs and reported a value of 0.810 (0.000), 25 which is close to the LGP value. However, this study, as well as those that used LIC and solid-state detectors, as shown in Figure 8, suggested a higher OF 4 value of approximately 0.826.…”
Section: Discussionmentioning
confidence: 72%
“…The OF 4 value obtained using EBT films agreed with the LGP value (Figure 8). Cyriac et al measured OF 4 using T60019 and the TRS-483 OCFs and reported a value of 0.810 (0.000), 25 which is close to the LGP value. However, this study, as well as those that used LIC and solid-state detectors, as shown in Figure 8, suggested a higher OF 4 value of approximately 0.826.…”
Section: Discussionmentioning
confidence: 72%
“…The coordinate of the RFP was defined as the midpoint between the half‐maximum of the rising and of the falling edge in the respective dose profiles. The PPS center for the scintillator and microdiamond was corrected for detector positioning errors based on CBCT imaging, as suggested by a recent publication 18 …”
Section: Methodsmentioning
confidence: 99%
“…The PPS center for the scintillator and microdiamond was corrected for detector positioning errors based on CBCT imaging, as suggested by a recent publication. 18…”
Section: Rfp/pps Coincidence Checkmentioning
confidence: 99%
“…For small field dosimetry, it is crucial to determine the field output correction factor kQmsr,Qclinfmsr,fclin$k_{{Q}_{msr},\ {Q}_{clin}\ }^{{f}_{msr},\ {f}_{clin}}$ to be able to correct the detector's reading and account for the abovementioned nonequilibrium conditions in machine‐specific reference f msr (msr) and clinical fields f clin (clin) with beam qualities Q msr and Q clin . Together with the field output factor (OF) normalΩQmsr,Qclinfmsr,fclin${{\Omega}}_{{Q}_{msr},\ {Q}_{clin}}^{{f}_{msr},{f}_{clin}}$ determination, these were the focus of investigation performed by different groups 2–11 . OF and field output correction factor determination for different detectors can be performed by measurements or with Monte Carlo (MC) simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Together with the field output factor (OF) determination, these were the focus of investigation performed by different groups. 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 OF and field output correction factor determination for different detectors can be performed by measurements or with Monte Carlo (MC) simulations. In general, field output correction factors are a product of four different perturbations in the small field; ratios of water‐to‐detector‐medium stopping powers in the clinical and machine‐specific reference field, volume averaging, fluence, and of spectral perturbations in clinical and machine‐specific reference fields.…”
Section: Introductionmentioning
confidence: 99%